Research Source Base of Primary Education in 1940-s – 1980-s - Lyudmyla Bondar (Pedagogical Discourse, 2013)
The content of primary school education in 1940-s – 1980-s has been characterized in the article. In particular on the basis of the analysis of different types of educational establishments, documents, state educational policy, changes in the structure, content of primary education have been determined and their development have been revealed. Taking into account the fact that the content of education is realized through the educational subjects (language, mathematics, natural studies etc.), the question about differentiated approach in its content appears. It must be compulsory principle of primary school functioning. It is shown in the article that the content of primary education is differentiated depending on the type of school, and the outer differentiation (at the level of the subject content and different means of its mastering organization) has been revealed.